Facets of Democracy: An Overview - Kharel, Aswasthama Bhakta (Molung Educational Frontier, 2019)
Democracy allows the expression of political preferences of citizens in a state. It advocates the rule of law, constraints on executive’s power, and guarantees the provision of civil liberties. It also manages to ensure human rights and fundamental freedoms of people. In democracy, people are supposed to exercise their freely expressed will. Ordinary people hold the political power of the state and rule directly or through elected representatives inside a democratic form of government. Democracy is a participatory and liberal way of governing a country. Different countries in the world have been practicing various models of democracy. There remains the participation of people in government and policy-making of the state under democracy. But when the majority can pull the strings of the society without there being legislation for protecting the rights of the minority, it may create a severe risk of oppression. Many countries of the world at the present time are facing democratic deficits. In several countries, the democratic practices are not adequately regulated and governed, as a result, the rise of violations of rules of law is observed. Even a few countries practicing democracy are not living peacefully. This situation has put a significant question about the need and sustainability of democracy. Democracy is a widely used system of governance beyond having several challenges. Here the concept, origin, models, dimensions, practices, challenges, solutions, and future of democracy are dealt to understand the structure of ideal democracy.